Aflatoxin Production in Meats. I. Stored Meats - Bullerman, Lloyd B. (1969)
Aflatoxins were produced on fresh beef (in which bacterial spoilage was delayed with antibiotics), ham, and bacon inoculated with toxinogenic fungi and stored at 15, 20 and 30 C. Meats stored at 10 C were spoiled by bacteria and yeast before detectable levels of aflatoxins were produced. High levels of aflatoxins were formed in meats stored at 20 C; one sample supported the production of 630 μg of aflatoxins per g of meat, the major portion (580 μg) of which was aflatoxin G(1). Meats stored below 30 C developed higher levels of aflatoxin G(1) than B(1), but at 30 C Aspergillus flavus produced equal amounts of B(1) and G(1), whereas A. parasiticus continued to produce more G(1) than B(1).